2022
DOI: 10.1128/spectrum.00979-22
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response and Plant Growth Promoting Activity of Pseudomonas fluorescens DR397 under Drought Stress Conditions

Abstract: Drought is a serious abiotic stress on plants as wells as the microbes that coexist with plants, which significantly lowers their fitness. The plant-bacterial interaction is an important strategy to enhance their fitness under drought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
(69 reference statements)
1
9
1
Order By: Relevance
“…It is due to that Si plays a role in reducing the effect of stress on the plant, as previously mentioned. This agrees with (Melo et al, 2022 andNishu et al, 2022), who studied the role of rhizobia on plants under water stress conditions, they found that rhizobia has an effective role in the production of stress proteins to survive under harsh environments particularly drought.…”
Section: Fruits Biochemical Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…It is due to that Si plays a role in reducing the effect of stress on the plant, as previously mentioned. This agrees with (Melo et al, 2022 andNishu et al, 2022), who studied the role of rhizobia on plants under water stress conditions, they found that rhizobia has an effective role in the production of stress proteins to survive under harsh environments particularly drought.…”
Section: Fruits Biochemical Contentsupporting
confidence: 90%
“…As a result, they could also function as PGPR in non-nodulating plants. Antioxidants, catalase, osmolytes, stress proteins, and exopolysaccharides are most likely produced by rhizobia to survive under harsh environments particularly drought (Melo et al, 2022;Nishu et al, 2022 andUzma et al, 2022). However, rhizobia have been observed to survive under drought up to −1.25 MPa .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most papers about crops inoculated with other P. fluorescens strains (such as DR397, P22, Pseudomonas sp. Z6, and P. fluorescens biotype G) [ 35 , 36 , 47 ] identify an increase in shoot dry biomass 2–4 times lower than our findings, even if higher plant yields were obtained.…”
Section: Discussioncontrasting
confidence: 75%
“…Among these, Pseudomonas fluorescens complex Migula, 1895 are ubiquitous in rhizospheric microbiota [ 31 ] and tolerant to metals [ 32 , 33 ]. These bacterial strains were also able to increase crop yield (e.g., Solanum tuberosum L.) [ 34 ], growth parameters (e.g., Pisum sativum L., up to 45%; Phaseolus vulgaris L., up to 20%) [ 35 ], and shoot dry biomass (e.g., Eragrostis tef (Zucc) Trotter, up to 2.8-fold) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some PGP microbes improve plant growth by solubilizing insoluble phosphates in the soil, particularly in phosphorus-deficient environments, thereby increasing phosphorus cycling and improving soil quality. Many bacterial strains, including Pseudomonas (Singh et al 2021 ; Asaf et al 2018 ; Saha et al 2022 ; Rikame and Borde 2022 ; Nishu et al 2022 ), Enterobacter (Guo et al 2020 ; Raturi et al 2022 ), and Serratia (Adam et al 2016 ), promote plant growth by improving nutrient availability. In the present study, we showed that an isolated strain ATSA2 T from surface-sterilized seeds produces a relatively high IAA content in the presence of l -tryptophan, with detectable siderophore and phosphate solubilization activity (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%